A message from our CEO about the future of Stack Overflow and Stack Exchange. Read now.

New answers tagged

0

The two formulations seem to be exactly the same. If I take the equations from the first method: $w_{D1}*\Delta_{D1} + w_{D2}*\Delta_{D2} = -2$ $w_{D1}*\Gamma_{D1} + w_{D2}*\Gamma_{D2} = -3$ And substitute for delta and gamma of the two options: $-w_{D1}+ 5 w_{D2}= -2$ $2w_{D1} -2w_{D2} = -3$ which after shifting the constants to the left becomes ...


Top 50 recent answers are included